# Prove that : \[{\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 2{\left( {\sin {\text{A}}} \right)^2} - 1 = 1 - 2{\left( {\cos {\text{A}}} \right)^2}\]

Last updated date: 24th Mar 2023

•

Total views: 310.2k

•

Views today: 3.87k

Answer

Verified

310.2k+ views

Hint- Here, we will be using formula ${a^2} - {b^2} = \left( {a - b} \right)\left( {a + b} \right)$ and identity ${\left( {\sin x} \right)^2} + {\left( {\cos x} \right)^2} = 1$.

To prove: \[{\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 2{\left( {\sin {\text{A}}} \right)^2} - 1 = 1 - 2{\left( {\cos {\text{A}}} \right)^2}\]

Let us simply the left most side of the above equation, we get

\[{\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left[ {{{\left( {\sin {\text{A}}} \right)}^2}} \right]^2} - {\left[ {{{\left( {\cos {\text{A}}} \right)}^2}} \right]^2}\]

Using formula ${a^2} - {b^2} = \left( {a - b} \right)\left( {a + b} \right)$, we get

\[ \Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left[ {{{\left( {\sin {\text{A}}} \right)}^2}} \right]^2} - {\left[ {{{\left( {\cos {\text{A}}} \right)}^2}} \right]^2} = \left[ {{{\left( {\sin {\text{A}}} \right)}^2} - {{\left( {\cos {\text{A}}} \right)}^2}} \right]\left[ {{{\left( {\sin {\text{A}}} \right)}^2} + {{\left( {\cos {\text{A}}} \right)}^2}} \right]\]

Now applying identity ${\left( {\sin x} \right)^2} + {\left( {\cos x} \right)^2} = 1$, we get

\[

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = \left[ {{{\left( {\sin {\text{A}}} \right)}^2} - {{\left( {\cos {\text{A}}} \right)}^2}} \right]\left[ 1 \right] = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} \\

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2}{\text{ }} \to {\text{(2)}} \\

\]

Now let us represent the complete RHS of equation (2) in terms of sine trigonometric function alone.

This can be done by using the identity ${\left( {\sin x} \right)^2} + {\left( {\cos x} \right)^2} = 1 \Rightarrow {\left( {\cos x} \right)^2} = 1 - {\left( {\sin x} \right)^2}$

\[

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = {\left( {\sin {\text{A}}} \right)^2} - \left[ {1 - {{\left( {\sin {\text{A}}} \right)}^2}} \right] = {\left( {\sin {\text{A}}} \right)^2} - 1 + {\left( {\sin {\text{A}}} \right)^2} \\

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 2{\left( {\sin {\text{A}}} \right)^2} - 1{\text{ }} \to {\text{(3)}} \\

\]

Now let us represent the complete RHS of equation (2) in terms of cosine trigonometric function alone.

This can be done by using the identity ${\left( {\sin x} \right)^2} + {\left( {\cos x} \right)^2} = 1 \Rightarrow {\left( {\sin x} \right)^2} = 1 - {\left( {\cos x} \right)^2}$

\[

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = \left[ {1 - {{\left( {\cos {\text{A}}} \right)}^2}} \right] - {\left( {\cos {\text{A}}} \right)^2} = 1 - {\left( {\cos {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} \\

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 1 - 2{\left( {\cos {\text{A}}} \right)^2}{\text{ }} \to {\text{(4)}} \\

\]

Now combining equations (3) and (4), we can write

\[{\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 2{\left( {\sin {\text{A}}} \right)^2} - 1 = 1 - 2{\left( {\cos {\text{A}}} \right)^2}\]

The above equation is the required equation which needs to be proved.

Note- In these types of problems, we simplify the one side of the equation which needs to be proved keeping in mind the trigonometric functions in which the final terms need to be represented.

To prove: \[{\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 2{\left( {\sin {\text{A}}} \right)^2} - 1 = 1 - 2{\left( {\cos {\text{A}}} \right)^2}\]

Let us simply the left most side of the above equation, we get

\[{\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left[ {{{\left( {\sin {\text{A}}} \right)}^2}} \right]^2} - {\left[ {{{\left( {\cos {\text{A}}} \right)}^2}} \right]^2}\]

Using formula ${a^2} - {b^2} = \left( {a - b} \right)\left( {a + b} \right)$, we get

\[ \Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left[ {{{\left( {\sin {\text{A}}} \right)}^2}} \right]^2} - {\left[ {{{\left( {\cos {\text{A}}} \right)}^2}} \right]^2} = \left[ {{{\left( {\sin {\text{A}}} \right)}^2} - {{\left( {\cos {\text{A}}} \right)}^2}} \right]\left[ {{{\left( {\sin {\text{A}}} \right)}^2} + {{\left( {\cos {\text{A}}} \right)}^2}} \right]\]

Now applying identity ${\left( {\sin x} \right)^2} + {\left( {\cos x} \right)^2} = 1$, we get

\[

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = \left[ {{{\left( {\sin {\text{A}}} \right)}^2} - {{\left( {\cos {\text{A}}} \right)}^2}} \right]\left[ 1 \right] = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} \\

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2}{\text{ }} \to {\text{(2)}} \\

\]

Now let us represent the complete RHS of equation (2) in terms of sine trigonometric function alone.

This can be done by using the identity ${\left( {\sin x} \right)^2} + {\left( {\cos x} \right)^2} = 1 \Rightarrow {\left( {\cos x} \right)^2} = 1 - {\left( {\sin x} \right)^2}$

\[

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = {\left( {\sin {\text{A}}} \right)^2} - \left[ {1 - {{\left( {\sin {\text{A}}} \right)}^2}} \right] = {\left( {\sin {\text{A}}} \right)^2} - 1 + {\left( {\sin {\text{A}}} \right)^2} \\

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 2{\left( {\sin {\text{A}}} \right)^2} - 1{\text{ }} \to {\text{(3)}} \\

\]

Now let us represent the complete RHS of equation (2) in terms of cosine trigonometric function alone.

This can be done by using the identity ${\left( {\sin x} \right)^2} + {\left( {\cos x} \right)^2} = 1 \Rightarrow {\left( {\sin x} \right)^2} = 1 - {\left( {\cos x} \right)^2}$

\[

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = \left[ {1 - {{\left( {\cos {\text{A}}} \right)}^2}} \right] - {\left( {\cos {\text{A}}} \right)^2} = 1 - {\left( {\cos {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} \\

\Rightarrow {\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 1 - 2{\left( {\cos {\text{A}}} \right)^2}{\text{ }} \to {\text{(4)}} \\

\]

Now combining equations (3) and (4), we can write

\[{\left( {\sin {\text{A}}} \right)^4} - {\left( {\cos {\text{A}}} \right)^4} = {\left( {\sin {\text{A}}} \right)^2} - {\left( {\cos {\text{A}}} \right)^2} = 2{\left( {\sin {\text{A}}} \right)^2} - 1 = 1 - 2{\left( {\cos {\text{A}}} \right)^2}\]

The above equation is the required equation which needs to be proved.

Note- In these types of problems, we simplify the one side of the equation which needs to be proved keeping in mind the trigonometric functions in which the final terms need to be represented.

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Write a letter to the Principal of your school to plead class 10 english CBSE